Analysis of the financial performance of village fund allocation management based on the growth ratio and effectiveness ratio at the bandar agung village office Ulu manna sub-district - Ela Julaili Putri; E. Ahmad Soleh; Yun Fitriano (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
The data sources used were primary data sources and secondary data from the Village APBDes of Bandar Agung Village, Ulu Manna Sub-District, South Bengkulu Regency. Based on the results of existing data processing, the effectiveness ratio based on the calculation of the Effectiveness Ratio it can be seenthat the Village Fund Allocation Effectiveness Ratio (ADD) for the village office in 2018 was 98.83%, in 2019 it was 99.20%, in 2020 it was 99.66%, and in 2021 it was 100% and in 2022 it was 99.88%. The effectiveness of the financial performance of the Village Fund Allocation (ADD) of the Bandar Agung Village office for 2018-2022 is categorized as Effective according to the financial performance in the village. While the growth ratio from the results of data processing, it was found that the Village Fund Allocation Revenue Growth Ratio (ADD) for the finance of the office in 2018 was 0% or normal, while in 2019 it was(-0.58%), and in 2020 it experienced another increase, namely (14.90%). In 2021 it decreased by 5.06% and in 2022 it increased by 18.47%.